Immune to Situation: The Self-Serving Bias in Unambiguous Contexts - Wang, Xiaoyan; Zheng, Li; Li, Lin; Zheng, Yijie; Sun, Peng; Zhou, Fanzhi A.; Guo, Xiuyan (Frontiers in Psychology, 2017)
Traditionally the self-serving bias was investigated in ambiguous context where participants worked on tasks measuring novel abilities before made attributions without clear criteria for success or failure feedbacks. Studies have confirmed that the self-serving bias is pervasive in the general population but demonstrates significant variability across situation in ambiguous context. The present study introduced an unambiguous context constituted by implicit causality interpersonal events (self played as an actor or recipient), whose inherent logic suggests attribution criteria. Our goal was to explore whether there was the self-serving bias in unambiguous context and examine whether the self-serving bias was sensitive to situation similarly in ambiguous context. Results showed that participants manifested the self-serving bias in attribution for negative interpersonal events in unambiguous context. The self-serving bias was greater in actor condition relative to recipient (study 1). This effect was not affected by the level of self-awareness which was manipulated by using camera or not during the experiment (study 2). Our findings provided evidence for the existence of the self-serving bias in unambiguous context. The self-serving bias was immune to situation in unambiguous context, but rather it depended upon factors associated with the events per se, such as the actor versus recipient role self played in interpersonal events.